Wintertime North Pacific Teleconnection Patterns: Seasonal and Interannual Variability - Yuan, Jiacan; Tan, Benkui; Feldstein, Steven B.; Lee, Sukyoung (Journal of Climate, 2015)
The teleconnections of the wintertime North Pacific are examined from the continuum perspective with self-organizing map (SOM) analysis. Daily ERA-Interim data for the 1979-2011 period are used. It is found that most of the North Pacific teleconnections can be grouped into several Pacific-North American (PNA)-like, western Pacific (WP)-like, and east Pacific (EP)-like SOM patterns. Each of the SOM patterns has an e-folding time scale of 7-10 days.The WP-like SOM patterns undergo a decline in their frequency from early to late winter, and vice versa for the EP-like SOM patterns, corresponding to an eastward seasonal shift of the North Pacific teleconnections. This seasonal shift is observed for both phases of the WP and EP patterns, and is only weakly sensitive to the phase of El Nino-Southern Oscillation. It is shown that the interannual variability of the PNA, WP, and EP can be interpreted as arising from interannual changes in the frequency of the corresponding SOM patterns. The WP- and EP-like SOM patterns are found to be associated with statistically significant sea ice cover anomalies over the Sea of Okhotsk and the Bering Sea. The low-level wind and temperature anomalies associated with these patterns are consistent with the changes in sea ice arising from both wind-driven sea ice motion and freezing and/or melting of sea ice due to horizontal temperature advection. Furthermore, widespread precipitation anomalies over the North Pacific are found for all three patterns. Chinese NSF [41130962, 41375060]; China Postdoctoral Science Foundation [2013M540014]; National Science Foundation [AGS-1139970, AGS-1036858, AGS-1401220]; National Oceanic and Atmospheric Administration [NA14OAR4310190] SCI(E) ARTICLE bktan@pku.edu.cn 20 8247-8263 28